Digitally reconstructed severe trauma-induced oro-maxillofacial defects with free vascularised composite tissue flaps. Issue 6 (July 2022) - Jiang, Canyang; Huang, Jianping; Lin, Lisong; Lin, Yuerong; Shi, Bin; Huang, Li
Abstract: The aim of this study was to outline the characteristics of severe trauma-induced oro-maxillofacial defects and explore the application of microsurgical reconstruction of these defects by selecting appropriate free vascularised composite tissue flaps. A retrospective analysis was performed in 11 cases with severe trauma-induced oromaxillofacial defects from 2005 to 2018, All cases were reconstructed with free vascularised composite flaps using a supermicro-surgical/micro-surgical and digital technology. This study consisted of 11 patients (8 men, 3 women) with a median age (range) of 28 (6–64) years. Patients with long-standing trauma experienced severe scars and displacements. The trauma-induced oro-maxillofacial defects ranged in size from 4.0 × 5.0 cm 2 to 7 × 15 cm 2 . Six radial forearm flaps, three fibular osteocutaneous flaps, a lateral thoracic flap, and an anterolateral thigh flap were harvested individually. All patients were treated effectively and followed up for over two years, with a 100% survival rate of these free vascularised composite tissue flaps. No uncontrollable complications occurred, and all patients were satisfied with the postoperative shape and function. The trauma-induced oro-maxillofacial defects display unique features, and microsurgical techniques play an important role in the reconstruction of shapes and function. In addition, some patients may need multi-stage surgeries to attain aesthetic refinement.